The Risk of Overweight and Obesity Among Latter-Day Saints - Mason, Philip B. (Review of religious research, 2013)
Despite evidence of the salutary effects of religion on physical health, relatively little attention has been paid to the influence of religiosity on the risk of overweight and obesity. Our study examines this relationship with specific attention to the influence of Latter-day Saint (LDS, Mormon) affiliation and attendance on bodyweight status. Latter-day Saints make an excellent test case because LDS proscriptions against the consumption of alcohol, coffee, tea, and tobacco could lead to either a reduced risk of overweight and obesity by reinforcing a broader constellation of healthy habits or a greater risk of overweight and obesity by contributing to unhealthy behaviors (e.g., overeating) that are substituted for religiously proscribed substance use. Given the salience of gender in the LDS context and gender-specific differences in bodyweight status, our analyses are run separately for men and women. While LDS men exhibit a somewhat greater obesity risk, LDS women are especially likely to face overweight and obesity risks. These findings demonstrate that religiosity can, in some circumstances, undermine physical health and that conservative religions can compromise bodyweight in gender-specific ways.